2013
DOI: 10.1128/mcb.01003-12
|View full text |Cite
|
Sign up to set email alerts
|

The H19 Imprinting Control Region Mediates Preimplantation Imprinted Methylation of Nearby Sequences in Yeast Artificial Chromosome Transgenic Mice

Abstract: cIn the mouse Igf2/H19 imprinted locus, differential methylation of the imprinting control region (H19 ICR) is established during spermatogenesis and is maintained in offspring throughout development. Previously, however, we observed that the paternal H19 ICR, when analyzed in yeast artificial chromosome transgenic mice (YAC-TgM), was preferentially methylated only after fertilization. To identify the DNA sequences that confer methylation imprinting, we divided the H19 ICR into two fragments (1.7 and 1.2 kb), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 57 publications
2
11
0
Order By: Relevance
“…To demonstrate a role for postfertilization paternal allele-specific methylation activity at the endogenous locus, we narrowed its essential sequences in YAC-TgM (Figs 4 and 5) (Okamura et al, 2013b) and deleted them from the endogenous paternal H19 ICR. Although gametic methylation of the mutant, endogenous H19 ICR was not affected, its methylation level was diminished soon after fertilization (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To demonstrate a role for postfertilization paternal allele-specific methylation activity at the endogenous locus, we narrowed its essential sequences in YAC-TgM (Figs 4 and 5) (Okamura et al, 2013b) and deleted them from the endogenous paternal H19 ICR. Although gametic methylation of the mutant, endogenous H19 ICR was not affected, its methylation level was diminished soon after fertilization (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that the 1.7-kb 'ICR21' fragment covering CTCF sites 1 and 2 (Fig. 4A) was sufficient to recapitulate paternal allele-specific DNA methylation after fertilization in YAC-TgM (Okamura et al, 2013b). We thus generated a series of 5′-truncated H19 ICR fragments: the ICR4321S fragment, in which the 5′-end of the 2.9-kb H19 ICR fragment (766 bp) was deleted but all four CTCF sites remained; and the ICR432 fragment, which is 173 bp shorter than the ICR4321S fragment and lacks CTCF site 1 (Fig.…”
Section: Germline Methylation Of the Endogenous H19 Icr Is Inhibited mentioning
confidence: 99%
“…(26)(27)(28)(29)(30), predominantly methylates hemimethylated CpG dinucleotides in the genome, and is considered to be the key maintenance methyltransferase during cell division (29)(30)(31)(32)(33). The DNMT2 gene is the most highly conserved of the methyltransferases in eukaryotes, and has been identified in organisms that exhibit DNA methylation, as well as in those that do not (26)(27)(28)(29)(30). DNMT3a and DNMT3b primarily perform de novo methyl transfer reactions via interactions with transcriptional repressors.…”
Section: Dna Methylationmentioning
confidence: 99%
“…DNA was purified with the QIAquick PCR purification kit (Qiagen, Venlo, The Netherlands) and subjected to qPCR analysis. The endogenous H19 ICR and Necdin sequences were analyzed as positive and negative controls, respectively [56]. LCR-HS5 and 3’HS1 primer sets are as follows: …”
Section: Methodsmentioning
confidence: 99%